2000
DOI: 10.1096/fasebj.14.10.1455
|View full text |Cite
|
Sign up to set email alerts
|

VDR‐Alien: a novel, DNA‐selective vitamin D3receptor‐corepressor partnership

Abstract: The vitamin D receptor (VDR) is a transcription factor that transmits incoming 1,25-dihydroxyvitamin D(3) (1alpha,25(OH)(2)D(3)) signaling via combined contact with coactivator proteins and specific DNA binding sites (VDREs), which ultimately results in activation of transcription. In contrast, the mechanisms of transcriptional repression via the VDR are less well understood. This study documents VDR-dependent transcriptional repression largely via histone deacetylase (HDAC) activity. Direct, ligand-sensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 48 publications
3
84
0
Order By: Relevance
“…3 Alien was previously characterised as a corepressor for specific members of the nuclear hormone receptors such as the thyroid hormone and vitamin D3 receptor. 4 In line with this, we observed that Alien is capable to repress the transcriptional activity of members of the E2F transcription factor family suggesting a role for Alien as a corepressor also for cell cycle regulated genes. 3 The aim of the present study was to detect in vivo further specific interacting partners of endogenously expressed Alien.…”
Section: Introductionsupporting
confidence: 81%
“…3 Alien was previously characterised as a corepressor for specific members of the nuclear hormone receptors such as the thyroid hormone and vitamin D3 receptor. 4 In line with this, we observed that Alien is capable to repress the transcriptional activity of members of the E2F transcription factor family suggesting a role for Alien as a corepressor also for cell cycle regulated genes. 3 The aim of the present study was to detect in vivo further specific interacting partners of endogenously expressed Alien.…”
Section: Introductionsupporting
confidence: 81%
“…*P50.05 cancer and PC-3 and DU-145 cells display many alterations that are associated with metastatic androgen-independent cancer, including aberrant p53 function and dysregulation of normal apoptotic responses (Carrol et al, 1993;Ewing et al, 1995;Isaacs et al, 1994;Tamimi et al, 1996;Mackey et al, 1998) and furthermore do not readily undergo apotosis when exposed to 1a,25(OH) 2 D 3 Zhuang and Burnstein, 1998). Interestingly, Carlberg and co-workers have demonstrated that either di erent VDR co-repressors complexes or structurally di erent vitamin D 3 analogs demonstrate VDRE selectivity (Quack and Carlberg, 1999;Nayeri and Carlberg, 1997;Danielsson et al, 1997;Polly et al, 2000). These ®ndings would allow for di erential regulation of genes by 1a,25(OH) 2 D 3 , within the same cell line, and disruption of a speci®c co-factor, such as a co-repressor with associated HDAC activity, would consequently silence a speci®c subset of 1a,25(OH) 2 D 3 -responsive genes.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that cofactors which have been described to repress other NRs, such as Alien (Dressel et al 1999, Polly et al 2000, PSF (polypyrimidine tract-binding protein) (Mathur et al 2001), and SUN-CoR (small unique nuclear receptor corepressor) (Zamir et al 1997), might also modulate ERα activity.…”
Section: Identification Of Er␣ Corepressorsmentioning
confidence: 99%